Fabrication of composite magnetic HAP/GO-PES membrane for iron removal: article - Roslan, Luqman; Othman, Nur Hidayati (2018)
Polymeric based membrane usually having problems with fouling and hydrophilicity of it surface. Thus, a new material which is graphene oxide (GO) was introduced to reduce the fouling effect. GO which obtained from the modified Hummers method is bind to the polymeric membrane. The magnetic NPs and hydroxyapatite (HAP) was added into the GO-PES membrane to form GO-MHAP-PES membrane. The membranes were fabricated using phase inversion technique and embedded with various percentage of GO (0.5, 1.0, 1.5 and 2.0 wt%). The effect of GO-MHAP-PES membrane morphology and performance were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), water contact angle, and Fourier Transform infrared (FTIR). The fabricated membrane display higher rejection rate compared to the bare.